The Influence of Discovery Learning Model on Students' Learning Outcomes in Social Studies - Dea Tami Restu Bumi; Sri Buwono; Venny Karolina; Hadi Wiyono; Thomy Sastra Atmaja (Edumaspul: Jurnal Pendidikan, 2023)
This research aimed to determine the influence of the discovery learning teaching model on the learning outcomes of seventh-grade students in the subject of Social Studies. The study employed a quantitative approach with a quasi-experimental design, involving both a control group (lecture-based teaching model) and an experimental group (discovery learning model). The research yielded results that indicated no significant influence of the lecture-based learning model on learning outcomes, as evidenced by the paired sample t-test with a two-tailed significance value of 8.728, which is higher than 0.05. Furthermore, the study demonstrated a significant influence of the discovery learning teaching model on students' learning outcomes, as confirmed by the Wilcoxon test, which showed a two-tailed significance value of 0.016, lower than 0.05. This research finding also indicated a significant impact of the discovery Learning teaching model on learning outcomes, with an effect size of 0.977, categorizing it as a medium effect